Deep-ultraviolet Raman scattering studies of monolayer graphene thin films. (January 2015) - Liu, Hsiang-Lin; Siregar, Syahril; Hasdeo, Eddwi H.; Kumamoto, Yasuaki; Shen, Chih-Chiang; Cheng, Chia-Chin; Li, Lain-Jong; Saito, Riichiro; Kawata, Satoshi
Abstract: We present joint experimental and theoretical investigations of the deep-ultraviolet Raman scattering spectra of monolayer graphene thin films. We found that upon a 266 nm laser excitation, while the G mode remains pronounced, the G ′ mode is not observed. The G ′ mode exhibits distinctive linewidth broadening towards the ultraviolet frequency region. The peak intensity ratio of the G ′ and G modes increases dramatically excited at 355, 532, and 785 nm wavelengths. All of the experimental findings are in good agreement with the theory calculated by the tight-binding method. We theoretically show that the integrated intensity of the G ′ mode is inversely proportional to the incident photon energy, whereas that of the G mode increases as the fourth power of the incident photon energy. These results extend our understanding of the double resonance Raman scattering process of graphene away from the Dirac cones and provide the foundation for future technologically important developments of graphene in the deep-ultraviolet frequency range.